Filmora Video Editing Application Training to Improve Students' Ability to Make Learning Videos in the Unima Sociology Education Study Program - Mesra, Romi; Monica, Waode Santa; Anton, Erning Ertami; Sukini, Sukini; Ritawati, Ritawati; Ngumarno, Jayus; Handaru, Calista Devi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
This service is carried out to improve the competency of students in the Unima Sociology Education Study Program, especially as well as students outside Unima who are interested in taking part in this training with the aim of being able to understand how to use the Filmora editing application to create learning videos and in fact this competency can also be used as a basis for becoming a content creator. The methods used in this activity include lectures, discussions, questions and answers and of course direct practice. After carrying out the training, it can be concluded that there are several steps in implementing this training, namely making and distributing electronic pamphlets, several things directed by the lecturer regarding tools and materials that must be prepared by participants are (bring a laptop, install the Filmora application on the participant's laptop, prepare a learning video will be edited), implementation of training (checking participants' software and hardware completeness, opening the Filmora video editing application, uploading videos, adding videos to projects, adding video text, dividing videos, adding filters, adding overlays, adding elements, adding split screens, adding sound background, exporting video).